(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2022)
The pandemic has led to a decrease in physical activity due to health measures and a significant increase in the time spent using mobile devices for various functions. Objective: to compare and relate the levels of physical activity and time spent using smartphones. Method: the instruments used for data collection were the International Physical Activity Questionnaire (IPAQ) in its short version validated in the Chilean context and the application “Screen time, restriction and parental control” available for Android and iPhone users. The first sample was composed of 127 students and the second sample collected one month later reached a number of 68 students. Results: The main findings of this study were that more than 60% of the Physical Education Pedagogy students who participated in this research present moderate and high levels of physical activity during the two measurements. The average daily time of smartphone use during the two measurements remained at an average of more than 350 minutes per day. For the purposes of this study there was no correlation between physical activity levels and smartphone usage time. Conclusion: More than 70% of the students meet the WHO physical activity recommendations during the two measurements. Smartphone usage time is moderate in the two measurements and did not influence students’ physical activity practice.